The potential in bridging the gap between architectural design and facilities management: From a knowledge management perspective - Rizal Husin,; Mohd. Zulakhmar Zakiyuddin, (Penerbit UKM, 2008)
The advantages of the Information Technology and Internet have opened up a transformation into collective intelligence societies linked to digital communication, particularly to the developing countries and the world in general. In the context of architectural design and facilities management, the changing trend of CAD solutions towards knowledge based has offered a new dimension for both practices. This paper aims to stimulate discussion on Knowledge Management (KM) approach towards a more informative and knowledge rich built environment and the potential of Internet enabled Computer Aided Design (iCAD) as a tool in achieving better facilities management. The approach is by increasing the realisation on the importance of knowledge management skills in both building professionals and reviewing the evolution of iCAD as the current tools in the practices. The main intention of this approach is to provide wider entrée to information and human resources, collective learning and sharing of knowledge between the building professionals